The Determinants of Bid-Ask Spreads in the Foreign Exchange Futures Markets: A Microstructure Analysis - DING, David K. (Institutional Knowledge at Singapore Management University, 1999)
This paper investigates and analyzes the intraday and daily determinants of bid-ask spreads in the foreign exchange futures market. It is found that the number of transactions is negatively related to the BAS, whereas volatility in general is positively related to it. The study also finds that there are economies of scale in trading FXF contracts. The intraday BAS follows a U-shaped pattern, and they tend to be higher on Mondays and Tuesdays than on other days of the week. Higher spreads at the beginning and end of a trading day are consistent with the presence of adverse selection and the avoidance of the possibility of carrying undesirable inventory overnight, respectively. Seasonal differences in BASs that are related to the delivery date of a contract are also found.